A strain of Talaromyces assiutensis provides multiple protection effects against insect pests and a fungal pathogen after endophytic settlement in soybean plants - Li Sui; Yang Lu; Ke Cheng; Yifan Tian; Zhiming Liu; Zhao Xie; Zhengkun Zhang; Qiyun Li (Biological Control)
Talaromyces assiutensis was reported as an endophytic fungi of plant, with antimicrobial and anticancer properties; however, it has never been reported as an entomopathogenic fungus (EPF). Herein, an EPF strain was isolated from diseased larvae of Spodoptera litura in a soybean field. The purified isolate was identified as T. assiutensis and designated TaS1GZL-1. Its pathogenicity towards five insect pests belonging to Lepidoptera and Hemiptera, as well as the effect of temperature on its growth and pathogenicity against insects were measured. In addition, its control efficiency against major soybean insect pests and phytopathogenicity were also evaluated after plant colonization. The results showed that TaS1GZL-1 had strong pathogenicity towards five insect pests, and there was no negative effect on the strain growth rate and the corrected mortality rate toward insect pests at 40 °C. Furthermore, this EPF strain could not only inhibit the growth of Sclerotinia sclerotiorum in vitro, but also colonized soybean plants as an endophyte via root irrigation. TaS1GZL-1 colonization upregulated the expression levels of 12 genes related to defense pathways in soybean lateral roots, thereby inducing plant tolerance against phytopathogen infection, as well as disrupting the feeding selectivity of S. litura larvae. Semi-field experiments verified that TaS1GZL-1 had practical control effects on S. litura larvae and sclerotinia disease. This is the first record of a natural infection of insect pests by T. assiutensis, providing new insights into its ecological function. Thus, TaS1GZL-1 is an EPF strain that directly kills a broad-spectrum of insect pests and induces plant tolerance against biotic stress caused by phytopathogens and insect pest after endophytic settlement in soybean plants.